The Soret absorption band of isolated chlorophyll a and b tagged with quaternary ammonium ions1. Issue 39 (21st October 2015) - Stockett, Mark H.; Musbat, Lihi; Kjær, Christina; Houmøller, Jørgen; Toker, Yoni; Rubio, Angel; Milne, Bruce F.; Brøndsted Nielsen, Steen
<x xml:space="preserve">Abstract</x> The true colors of chlorophyll a and b, isolated in vacuo, are revealed from a combination of gas-phase ion spectroscopy and TD-DFT calculations.